DYNAMICS OF INDICATORS IN THE CELL-MEDIATED AND HUMORAL LINKS OF THE IMMUNE SYSTEM IN PATIENTS WITH THYROID CANCER - I.Yu. Bagmut; O.O. Galmiz (Проблеми екології та медицини)
This work is a fragment of research projects of Kharkiv Medical Academy of Postgraduate Education: “Cellular-molecular mechanisms of inflammation associated with chronic diseases”, the state registration number 015U001186, and “Pathochemical mechani sms of action of radioiodine on the organism and principles of their early diagnosis and correction”, state registration number 0117U000589. This paper studied cell-mediated and humoral immunity in patients with thyroid cancer (TC) in terms of evaluation of specific and non-specific immunological resistance of the organism. Non-specific immunological resistance of the body was studied on the basis of determining the phagocytic activity of neutrophils, indices of white and red blood cells. Analysis of the study allows us to judge that under the conditions of oncopathology of the thyroid gland, there is a suppression of the cellular link of the immune system (macrophages, monocytes, histiocytes, T-lymphocytes, dendritic cells) and intercellular mediator interactions that are associated with a decrease in the activity of humoral immune system, which was confirmed by a significant drop in the level of B-lymphocytes and immunoglobulins (JgG, Jg M, JgA). The results of the research revealed the inhibition of non-specific resistance of the body in patients with thyroid cancer, depending on the cellular structure of the tumor, which was characterized by a decrease in phagocytic activity of neutrophils. These changes took place against the background of the development of endogenous intoxication, pathogenic links of erythropoesis and methemoglobinemia.